Implementation of zoning to guide management of foot and mouth disease in Tunisia. Issue 3 (21st May 2021) - Mtaallah, Oumaima; Squarzoni‐Diaw, Cécile; Kalthoum, Sana; Bouguedour, Rachid; Muñoz, Facundo; Tran, Annelise; Coste, Caroline
Summary: The World Organisation for Animal Health advocates the zoning approach for the surveillance and monitoring of foot and mouth disease (FMD), a highly contagious animal disease. Our purpose is to implement the zoning approach in Tunisia by identifying existing natural and artificial barriers to the movement of live animals. A Geographic Information System (GIS)‐based MultiCriteria Evaluation approach was developed. Eight national and international experts were asked to identify the barriers and prioritize them, characterized by a percentage weight between 0 and 100. These barriers were mapped and combined, taking into account their relative importance, to create a friction map that makes it possible to visualize areas where animal movements are restricted. Uncertainty analysis was performed to assess the robustness of the model. The results showed that the selected barriers were in order of decreasing importance: maritime borders with a weight of 33.5%, rivers (13.8%), slopes equal to or greater than 10% (13.8%), wetlands (13.3%), forests (7.7%), land borders (7.7%), railway networks (5%) and main roads (4.9%). The Cap Bon zone is the only favourable zoning area for the control of FMD in Tunisia. A regional approach resulting from this work could be a major asset in identifying regions suitable for zoning in North Africa.